2019
DOI: 10.1213/xaa.0000000000001046
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Residency Training in Airway Management: A Competency-Based Model Curriculum

Abstract: The Accreditation Council for Graduate Medical Education (ACGME) is moving toward competency-based medical education. This educational framework requires the description of educational outcomes based on the knowledge, skills, and behaviors expected of competent trainees. An assessment program is essential to provide formative feedback to trainees as they progress to competency in each outcome. This article describes the development of 2 model curricula for airway management training (basic and advanced) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…A moderate amount of research has looked at the impact of adding dedicated airway management rotations into anesthesiology curriculum [ 7 , 9 , 21 ], focusing particularly on difficult cases, but little has looked at the impact of an OR-based airway rotation on subsequent performance of nonanesthesiology residents, despite the frequent use of anesthesiology airway rotations to expand the training and clinical case volume for nonanesthesiology programs [ 57 , 58 ]. Soleimanpour and colleagues [ 59 ] examined the impact of a 36-hour airway course on postgraduate year (PGY) 1 EM resident bag-mask ventilation and intubation success rates before and after an additional 1-month OR-based training program.…”
Section: Where Should This Take Place and Who Should Be Teaching?mentioning
confidence: 99%
See 1 more Smart Citation
“…A moderate amount of research has looked at the impact of adding dedicated airway management rotations into anesthesiology curriculum [ 7 , 9 , 21 ], focusing particularly on difficult cases, but little has looked at the impact of an OR-based airway rotation on subsequent performance of nonanesthesiology residents, despite the frequent use of anesthesiology airway rotations to expand the training and clinical case volume for nonanesthesiology programs [ 57 , 58 ]. Soleimanpour and colleagues [ 59 ] examined the impact of a 36-hour airway course on postgraduate year (PGY) 1 EM resident bag-mask ventilation and intubation success rates before and after an additional 1-month OR-based training program.…”
Section: Where Should This Take Place and Who Should Be Teaching?mentioning
confidence: 99%
“…If anesthesiologists are to continue as the airway experts, it has been suggested that to rethink not only their own training paradigms [7][8][9] but also how to include interactions with other specialties in training [10]. The methods for providing airway management training to nonanesthesiologists have taken multiple approaches.…”
mentioning
confidence: 99%
“…The required elements of a competency‐based pediatric airway management curriculum are goals, clearly defined learning objectives with expected educational outcomes, specific training experiences to achieve competency and assessment methods to document the achievement of the competencies …”
Section: Curriculum Design Interdisciplinary and Interprofessional mentioning
confidence: 99%
“…According to the interprofessional focus group of pediatric airway management teachers and learners that Weatherall's group established to examine educational approaches that feels the most useful for learners, an ideal pediatric airway management curriculum includes knowledge acquisition, rehearsal, supported hands‐on clinical exposure, and simulation to practice teamwork . A similar construct appears in the adult airway management curriculum designed for anesthesia residents published by Galway . Such competency‐based pediatric airway curriculum has not been published.…”
Section: Curriculum Design Interdisciplinary and Interprofessional mentioning
confidence: 99%
“…[14][15][16][17] A recent publication referenced a comprehensive airway assessment checklist for adult patients, but did not include a pediatric assessment and included no validity evidence. 18 Given the significant anatomic differences and equipment choices for use in pediatric patients, this adult assessment was not suitable to assess providers skills in pediatric patients. Our objective was to develop a comprehensive simulation-based tool for the formative assessment of resident pediatric airway skills performance and to evaluate the evidence for the tool's validity.…”
Section: Introductionmentioning
confidence: 99%